2020
DOI: 10.1080/14789949.2020.1746822
|View full text |Cite
|
Sign up to set email alerts
|

Social workers’ perspectives on people parenting while patients in a secure hospital

Abstract: who were involved in data collection in the larger study of which this was a part, practical support from all the clinical staff at Caswell Clinic and, in particular, for administrative assistance from Denise Jones and Michelle Matthews, and, above all from the considerable investment of time from the social workers themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Studies found clear benefit for training for professionals in supporting children of parents with mental health and/or substance use issues (Vigano et al, 2017) and across a range of social service settings (Featherstone & Broadhurst, 2003;Kemp et al, 2009;Gray et al, 2009, McConnell et al, 2011, Kalebic et al, 2020.…”
Section: System Responses and Issuesmentioning
confidence: 99%
“…Studies found clear benefit for training for professionals in supporting children of parents with mental health and/or substance use issues (Vigano et al, 2017) and across a range of social service settings (Featherstone & Broadhurst, 2003;Kemp et al, 2009;Gray et al, 2009, McConnell et al, 2011, Kalebic et al, 2020.…”
Section: System Responses and Issuesmentioning
confidence: 99%